English for Academic Purposes in a Brazilian Public Higher Education Institution: a needs’ analysis survey - BERGOLI , Pâmela Portal; BOCORNY , Ana Eliza Pereira; Pires de FREITAS, Ana Luiza (The ESPecialist, 2022)
This study focuses on raising the profile and needs of a Brazilian public Higher Education Institution (HEI) regarding the planning, program design, choice of courses, selection, and development of materials for English for Academic Purposes (EAP). The research is a case study comprising an online questionnaire with 346 respondents, about the community’s experiences and needs regarding English in an academic context. The results revealed that respondents aged between 20 and 30 years (73.6%), the prevalence of the female sex (68.7%), in the categories of undergraduate (52%) and graduate students (44.3%) perceive EAP as extremely important (74.3%) to read academic articles (96.6%), books and chapters (92.2%), attend lectures (72.4%) as well as write abstracts (71.0%). The data obtained is expected to improve the HEI’s IFA proficiency. Keywords: English for Academic Purposes, Case Study, Needs Assessment, Academic English